2020
DOI: 10.4236/as.2020.117040
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to No-Effect Concentration of Diazinon Induced Histological Lesions in Organs of <i>Clarias</i> <i>gariepinus</i>

Abstract: In all parts of the world pesticides have been found in the aquatic ecosystem and scientific evidence has also shown that they can enter the food chain. Diazinon is an organophosphate pesticide, widely used in agriculture to control a wide variety of suckling and leaf eating insects and recently in fish culture to suppress some parasitic diseases; nevertheless, there is little study on its adverse effect on fish. In this study, seventy-two (72) apparently healthy catfish comprising adult and juvenile of both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Physico-chemical analysis revealed that these effluents were highly toxic, not only to aquatic organisms but the entire web chain including human beings who are primary consumer of fish. Aquatic species have been deemed an outstanding and cost-effective model system because of their ability to concentrate, store, and metabolize water-borne contaminants (26) for analyzing the carcinogenic, mutagenic and toxic potential of pollutants (27) and (28). Fish exposed to chemical pollutants had a variety of lesions in various organs (29).…”
Section: Resultsmentioning
confidence: 99%
“…Physico-chemical analysis revealed that these effluents were highly toxic, not only to aquatic organisms but the entire web chain including human beings who are primary consumer of fish. Aquatic species have been deemed an outstanding and cost-effective model system because of their ability to concentrate, store, and metabolize water-borne contaminants (26) for analyzing the carcinogenic, mutagenic and toxic potential of pollutants (27) and (28). Fish exposed to chemical pollutants had a variety of lesions in various organs (29).…”
Section: Resultsmentioning
confidence: 99%